ENTREPRENEURIAL PASSION, ENTREPRENEURIAL ALERTNESS AND ISLAMIC ENTREPRENEURIAL ORIENTATION: ITS APPLICATION TO THE MUSLIMAH ENTREPRENEUR - Suswita Roza; Yayuk Sriayudha; Ade Octavia (Dinasti Publisher, 2020)
The success of an entrepreneur orientation from an Islamic perspective is not only measured in material success but also in a growing business. Muslimah entrepreneur needs passion and alertness in entrepreneurship to help to shape an entrepreneurial optimism and make decisions as well as business development efforts. The aims of the research are (1). Analyzing the influence of entrepreneurial passion on entrepreneurial alertness (2). Analyzing the influence of entrepreneurial alertness on Islamic entrepreneurial orientation (3). Analyzing the influence of entrepreneurial passion on Islamic entrepreneurial orientation. Data were collected from a sample of 86 Muslimah entrepreneurs from the Association of Muslimah Entrepreneurs in Jambi Province. Data collection is carried out using a questionnaire as the instrument research. Moreover, path analysis is used to analyze the influence of each variable studied. The results showed that there is a positive and significant influence between: entrepreneurial passion on entrepreneurial alertness, entrepreneurial alertness on Islamic entrepreneurial orientation, and entrepreneurial passion on the Islamic entrepreneurial orientation of Muslimah entrepreneurs. Research implementation will enhance the passion and alertness of Muslimah entrepreneurs and it suggests further studies to strengthen the model of research particularly in terms of Islamic entrepreneurship perspective.